Analisis Tingkat Kesulitan Belajar Siswa Kelas VII di SMP Negeri 1 Ciruas - Mulyawan, Galuh; Merisanti, Merisanti; Tazkiya, Rifa’atul; Rahmawati, Gita; Risyancik, Putri Audina (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
This study aims to determine the level of learning difficulties of seventh grade students at SMP Negeri 1 Ciruas. The study uses a quantitative approach with a descriptive type. The population and sample in this study are all 59 seventh grade students selected through total sampling techniques. Data were collected through a validated questionnaire and analyzed using descriptive statistical techniques by grouping the scores averages into categories of learning difficulty levels. The analysis results show that most students are in the moderate learning difficulty category, some are in the high category, and only a small portion are in the low category. The learning difficulties experienced by students include aspects of material comprehension, low learning motivation, and a lack of effective learning strategies. Based on these results, it is recommended that guidance and counseling teachers provide targeted services, both through classical that guidance and counseling teachers provide targeted services, both through classical guidance and individual counseling, and encourage collaboration with subject teachers to create learning that is appropriate for the students’ developmental stage. In addition, the school is advised to organize programs to improve learning abilities and create a learning environment that supports student development.